"Bearing the Pain": The Experience of Aging African Americans With Osteoarthritis Pain. (June 2020) - Booker, Staja Q.; Tripp-Reimer, Toni; Herr, Keela A.
Studies document that osteoarthritis-related joint pain is more severe in African American older adults, but research on the personal experience of osteoarthritis pain self-management in this population is limited. Using a qualitative descriptive design, our objective was to extend our understanding of the experience of life with osteoarthritis pain. Eighteen African Americans (50 years and older) were recruited from Louisiana to participate in a single semi-structured, in-depth interview. A conventional content analysis revealed that "Bearing the pain" characterized how older African Americans dealt with osteoarthritis. Bearing the pain comprised three actions: adjusting to pain, sharing pain with others, and trusting God as healer. We discovered that a metapersonal experience subsumes the complex biopsychosocial-cultural patterns and the intricate interaction of self, others, and God in living with and managing osteoarthritis pain. Study findings have implications for application of more inclusive self-management frameworks and interventions.